The planet on our plates: approaches to incorporate environmental sustainability within food-based dietary guidelines - Dooren, Corné van; Loken, Brent; Lang, Tim; Meltzer, Helle Margrete; Halevy, Sarah; Neven, Loes; Rubens, Kristof; Seves-Santman, Marije; Trolle, Ellen (Frontiers in Nutrition, 2024)
For many decades, food-based dietary guidelines (FBDGs) were only health-oriented. This changed post-2009 when gradually, an increasing number of countries began to include environmental sustainability considerations in their guidelines. International organisations such as the Food and Agriculture Organization (FAO) and the World Health Organization (WHO) have stated that governments should include environmental sustainability in future FBDGs. However, methodologies on how this should be done are lacking. Therefore, through workshops and discussions with experts, we analysed a selection of methodologies and classified them into six groups: (1) health first; (2) additional advice; (3) demonstrating synergies; (4) modelling impact; (5) combining strategies; (6) systems first. We then assessed how innovative each approach was and their potential for transformative impact. Of the 6 approaches investigated, only approaches 5 and 6 could be considered as disruptive innovations and leading to major changes. Adding environmental sustainability into FBDGs is a policy innovation and has become a debate between old and new multi-criteria guidelines for eating. With the addition of environmental sustainability in FBDGS, a new or emerging set of multi-criteria guidelines for judging food are being proposed that challenges past norms and governance. Today, there is growing scientific consensus that diets that are good for human health are also good for the environment. There is also a growing recognition that food system change is inevitable and desirable. We see this as a positive opportunity to collaborate on FBDGs that are more appropriate for the 21st century and ambitious enough to meet the environmental challenges at hand.